Ultrafast dynamics of laser-metal interactions in additive manufacturing alloys captured by in situ X-ray imaging - Aiden A. Martin; Nicholas P. Calta; Joshua A. Hammons; Saad A. Khairallah; Michael H. Nielsen; Richard M. Shuttlesworth; Nicholas Sinclair; Manyalibo J. Matthews; Jason R. Jeffries; Trevor M. Willey; Jonathan R.I. Lee (Materials Today Advances, 2019)
Advanced in situ characterization is essential for determining the underlying dynamics of laser-material interactions central to both laser welding and the rapidly expanding field of additive manufacturing. Traditional characterization techniques leave a critical experimental gap in understanding the complex subsurface fluid flow and metal evaporation dynamics inherent in laser-induced heating of the metal. Herein, in situ ultra-high-speed transmission X-ray imaging is revealed to be essential for bridging this information gap, particularly via comparison with and validation of advanced multiphysics simulations. Imaging on submicrosecond timescales enables correlation between dynamics of the laser-generated vapor–liquid interface and melt pool surface instabilities in industrially relevant alloys. X-ray imaging and complimentary simulations reveal vapor depression oscillations and rapid expansion due to reflection of the processing laser from the front surface of the vapor depression. Pore formation studies at steady state and during prompt removal of laser heating at the end of track reveal that the rapidly solidifying melt pool traps pores near the base of the vapor-filled depression. Moreover, pores within the melt pool are entrained by Marangoni convection which overcomes the force of buoyancy and forces the pores downward from the surface immediately before solidification. Observed solidification kinetics, consistent with previous results, give insight into surface morphology and porosity in the processed material. The information presented here is key for defining the physical models that describe laser-material interaction and ultimately increases our understanding of the emerging field of laser-based metal additive manufacturing. Keywords: Additive manufacturing, Laser processing, X-ray imaging, Multiphysics simulation, Pore formation